2019
DOI: 10.1002/macp.201800539
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Light‐Responsive Aliphatic Polycarbonate via Versatile Polycondensation for Controlled Degradation

Abstract: Starting from (2,2,5‐trimethyl‐1,3‐dioxan‐5‐yl)methanamine with light‐responsive 4,5‐dimethoxy‐2‐nitrobenzyl protecting groups, a variety of light‐responsive copolycarbonates (LrPCs) are synthesized by a general two‐step polycondensation using lithium acetylacetonate (LiAcac) as catalyst. UV/Vis, 1H nuclear magnetic resonance (NMR), and size exclusion chromatography (SEC) confirm the rapid decomposition of these polymers in response to irradiation with UV light. Stable and monodisperse nanoparticles with hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…By exploiting similar strategy, Kuckling and Sun have recently developed a new light‐responsive aliphatic polycarbonate (LrPC) for delivery of the photosensitizer 5,10,15,20‐tetrakis (m‐hydroxyphenyl)chlorin (mTHPC) ( Figure ). Multiple photocleavable oNB groups were conjugated within this LrPC polymer as side chains . UV light irradiation (λ = 320–480 nm) resulted in the cleavage of the oNB protecting groups, followed by the rapid degradation of the polymers via intramolecular cyclization.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…By exploiting similar strategy, Kuckling and Sun have recently developed a new light‐responsive aliphatic polycarbonate (LrPC) for delivery of the photosensitizer 5,10,15,20‐tetrakis (m‐hydroxyphenyl)chlorin (mTHPC) ( Figure ). Multiple photocleavable oNB groups were conjugated within this LrPC polymer as side chains . UV light irradiation (λ = 320–480 nm) resulted in the cleavage of the oNB protecting groups, followed by the rapid degradation of the polymers via intramolecular cyclization.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…Multiple photocleavable oNB groups were conjugated within this LrPC polymer as side chains. [38,55,56] UV light irradiation (λ = 320-480 nm) resulted in the cleavage of the oNB protecting groups, followed by the rapid degradation of the polymers via intramolecular cyclization. The light-induced reaction then led to the burst release of mTHPC.…”
Section: Light-degradable Polymers With Photocleavable Side Chainsmentioning
confidence: 99%
“…Similarly, Fang et al [146] reported photo-responsive micelles consisting of PNIPAM-b-poly(3-methyl-3-nitrobenzyl-trimethylene carbonate) for indomethacin drug delivery system. Likewise, Kuckilng and coworkers developed a series of light-degradable nanocarriers consisting of PEGylated APC with an o-nitrobenzyl ester group as side chains [147][148][149][150][151]. The nanoparticles were prepared from mixing amphiphilic APC copolymer with poly(lactide-co-glycolide) in ratio 1:3 (Figure 9).…”
Section: Light-responsive Apc Nanocarriersmentioning
confidence: 99%
“…from other stimuli whose control is limited by time and location, drug release triggered by light can be precisely modulated by selecting suitable irradiation parameters regarding light wavelength, intensity, irradiation time, and spatial resolution. [11][12][13] Several light-responsive polymeric systems used as drug carriers have been explored to rapidly release encapsulated payload in exposure to UV light. [14][15][16][17] Recently, a novel o-nitrobenzyl (ONB)functionalized light-responsive aliphatic polycarbonate (LrPC) has been used as drug carrier for photosensitizer 5,10,15,20-tetrakis(m-hydroxyphenyl) chlorin (mTHPC).…”
Section: Doi: 101002/marc201900348mentioning
confidence: 99%
“…Recently, PU nanoparticles with stimuli‐responsive properties, including pH, redox, and temperature sensitivity have been widely investigated as drug carriers. Differing from other stimuli whose control is limited by time and location, drug release triggered by light can be precisely modulated by selecting suitable irradiation parameters regarding light wavelength, intensity, irradiation time, and spatial resolution …”
mentioning
confidence: 99%